IMPACTS OF OPEN DUMPSITE LEACHATE ON SOIL ENZYMATIC ACTIVITY IN KANI-QRZHALA OPEN DUMPSITE – ERBIL CITY - bapeer, Suzan B.; Darwesh , Dalshad A. (Science Journal of University of Zakho, 2023)
The study was carried out to assess the effect of open dump site leachate on soil enzymes activity. Soil samples were collected in Kani-Qrzhala open dump site in Erbil city in four sites (Site1, Site2, Site3 and Site4) for different depths; surface ,30cm,60cm and 90 cm following the edge drainage pathway of leachate. The results of dehydrogenase, urease and catalase show a significant variation at significant levels (P⩽0.01) and (P⩽0.05) respectively. The highest rates of dehydrogenase, urease and catalase (77.69 µg TPF.g-1, 454.50 µg N.g-1, and 1.927µg H2O2.g-1), were recorded at surface point in all sites, while the lowest rates of all enzymes were recorded at 90 cm respectively, this is indicating that the soil depth adversely affected enzymes activity. Using oak tree wood and walnut shell biochar by 10% as a treatment to polluted soil, significantly increased enzymes activity. Walnut shell biochar was more suitable than oak tree wood biochar to catalase and urease activity, where urease was increased by 133.61% and catalase by 63.40%, while dehydrogenase activity was increased by 95.07% after using oak tree wood biochar which was more suitable than walnut shell biochar. This was related to the feedstock and technology production of biochar that affected on biochar structure and activity, however in this study, biochar application generally had a positive effect on enzymes activity and soil depth had an adverse effect.
Keywords: Soil enzyme; Biochar; Landfill; Leachate; Soil depth